2020
DOI: 10.3390/genes11060596
|View full text |Cite
|
Sign up to set email alerts
|

Pitt-Hopkins Syndrome: Clinical and Molecular Findings of a 5-Year-Old Patient

Abstract: Pitt Hopkins syndrome (PTHS) is a very rare condition and until now, approximately 500 patients were reported worldwide, of which not all are genetically confirmed. Usually, individuals with variants affecting exons 1 to 5 in the TCF4 gene associate mild intellectual disability (ID), between exons 5 to 8, moderate to severe ID and sometimes have some of the characteristics of PTHS, and variants starting from exon 9 to exon 20 associate a typical PTHS phenotype. In this report, we describe the clinical and mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…This change in protein expression supports a change in the pathway choice (right part of the model). In this cell type, p21 associates with PCNA ( 56 , 86 ) as well as POLι (Figure 6E ) and antagonizes PCNA poly-ubiquitination ( Supplementary Figure S5B ), triggering another DDT choice, most likely TLS, which mediates rapid but potentially mutagenic bypass of the replication barrier ( 48 ). Though the TLS bypass is active also in nd cells and fork decelerating mechanisms also in diff cells (stippled thin arrows), POLι keeps the balance such that slow replication dominates in nd and fast replication in diff cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This change in protein expression supports a change in the pathway choice (right part of the model). In this cell type, p21 associates with PCNA ( 56 , 86 ) as well as POLι (Figure 6E ) and antagonizes PCNA poly-ubiquitination ( Supplementary Figure S5B ), triggering another DDT choice, most likely TLS, which mediates rapid but potentially mutagenic bypass of the replication barrier ( 48 ). Though the TLS bypass is active also in nd cells and fork decelerating mechanisms also in diff cells (stippled thin arrows), POLι keeps the balance such that slow replication dominates in nd and fast replication in diff cells.…”
Section: Discussionmentioning
confidence: 99%
“…The p53 target p21 is well-known to play a multifaceted role in negatively and positively regulating DNA elongation and TLS, whereby its PCNA binding capacity is a prerequisite and its protein level of critical importance ( 28 , 36 , 56 , 58 , 86 , 87 ). Our single and double-kd experiments revealed that p21 exerts at least partially distinct functions from p53 in the DDT pathway choice.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of rare diseases is one of the most challenging areas of clinical genetics. Prior to this study, we believed that the DeepGestalt program would only be successful in the identification of common genetic conditions; however, it has also succeeded in identifying patients with rare genetic disorders (Gardner et al, 2017;Liehr et al, 2018;Arora et al, 2020;Pascolini et al, 2020;Tripon et al, 2020), as in our case. For the diagnosis of rare diseases, the input of clinical findings as well as facial gestalt analysis are recommended (Elmas and Gogus, 2020).…”
Section: Discussionmentioning
confidence: 85%
“…The presence of congenital microcephaly, characterized by a cranial perimeter of less than two standard deviations below the mean for age [13], is described in 18% of PTHS cases and is one of the main findings related to craniometry [2,12]. A brachycephalic skull shape has also been described by some authors but without a detailed definition that can corroborate the diagnosis of craniosynostosis [14]. Craniometry in both cases described herein ruled out microcephaly or brachycephaly, considering the vector patterns of Virchow's law [4,7].…”
Section: Craniosynostosis and Pitt-hopkins Syndromementioning
confidence: 99%